СУТНІСТЬ ПЕДАГОГІЧНИХ УМОВ ФОРМУВАННЯ КУЛЬТУРИ ЗДОРОВ’Я СТУДЕНТІВ МЕДИЧНИХ КОЛЕДЖІВ У ПОЗААУДИТОРНІЙ ДІЯЛЬНОСТІ - Шостак, Ігор (Збірник наукових праць Уманського державного педагогічного університету, 2020)
В статті розглядається обґрунтування педагогічних умов формування культури здоров’я студентів медичних коледжів у позааудиторній діяльності. Апробація власних педагогічних умов кореляційного взаємозв’язку теоретичної та практичної підготовки, розвитку самостійного самоврядування та спортивно-оздоровчої діяльності студентів медичного коледжу у позааудиторній діяльності сприятиме вирішенню проблематики дослідження формування культури здоров’я студентів медичних коледжів. В статье рассматривается обоснование педагогических условий формирования культуры здоровья студентов медицинских колледжей в внеаудиторной деятельности. Апробация собственных новых условий корреляционной взаимосвязи теоретической и практической подготовки, самостоятельного самоуправления и спортивно-оздоровительной деятельности студентов медицинского колледжа в внеаудиторной деятельности будет способствовать решению проблематики исследования формирования культуры здоровья студентов медицинских колледжей в внеаудиторной деятельности. In the article the substantiation of pedagogical conditions of formation of culture of health of students of medical colleges in extracurricular activities. Тesting their new environment correlation relationship of theoretical and practical training, self-government and sport and recreational activities of medical college students in extracurricular activities contribute to solving the problems of the research culture of health of students of medical colleges. In the future, earned theoretical knowledge of a culture of health and implemented student sports parliament must accumulate to exist in the activity of medical students in the sports sections, participation in regional and national sports day, tourist hiking, solving design problems that we According become a culture of health conditions of medical college students in extracurricular activities. However, it should also be noted that the above conditions are not educational panacea. You can not give up the search for new terms, given the lack of extracurricular technique is developed in high school.